Investigation of the Presence of Arachnoid Granulation in Fetuses and Early Infancy - Kahraman Ozlu, Eylem Burcu; Kayalar, Ali Erhan; Ertan, Yesim (Journal of Child Science, 2022)
The aim of our study is to investigate the importance of arachnoid granulation in cerebrospinal fluid physiology in fetuses and early infancy. Using the random sampling method, postmortem fetuses more than 26 weeks of gestation age and the children under the age of 1 year were chosen from the autopsy materials. Two male and two female intrauterine dead fetus; three male and three female, totally six children under the age of 1 year and one 3-year-old male were included in this study. In cases of intrauterine fetuses more than 26 weeks of gestation and children under the age of 1 year, complete invagination of arachnoid villi into the superior sagittal sinus was examined histologically. In the intrauterine period and in the first 6 months of life, arachnoid villi structures were not found in histologic preparations although in preparations taken after the 6 months of life samples showed similarities to arachnoid granulations. These structures were considered as arachnoid villi drafts after immunohistochemical analysis. In the control case who were 3 years old, maturation of arachnoid villi was complete and the arachnoid villi were invaginated into the superior sagittal sinus as fingerlike extensions. In our study, we think that the failure after E3V intervention in the treatment of hydrocephalus in cases under the age of 1 years may be related to the completion of arachnoid granulation development after the 18th month of life and the immature resorption capacity in this period.
Keywords: cerebrospinal fluid; arachnoid granulation; dural wall; anlage